2013
DOI: 10.1007/s13197-013-1162-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and enterotoxigenic profile of Bacillus cereus in meat and meat products of Uttarakhand, India

Abstract: The present investigation was undertaken to study the incidence and enterotoxigenicity of Bacillus cereus in raw meat and meat products. B. cereus was isolated from 29 (30.9 %) of the 94 samples analyzed. Recorded incidences of B. cereus from raw meat and meat products samples were 27.8 and 35 %, respectively. A high level of organism was found in cooked-meat (35 %) than raw meat samples (27.78 %) from 40 cooked-meat products and 54 raw meat samples analyzed. Screening of isolates by multiplex polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
68
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 34 publications
22
68
6
Order By: Relevance
“…In the present study results revealed the incidence of B. cereus isolates as 29.33 per cent in meat and meat products which are in agreement with similar incidence reported by Schlegelova et al, (2003) and Tewari et al, (2013), who too reported an incidence of 28 per cent and 30.9 per cent respectively in meat samples. However, Bedi et al, (2004) and Kamat et al, (1989) reported an incidence of 63.2 per cent and 80 per cent respectively in chicken and meat products.…”
Section: Antibiogram Of B Cereus Isolatessupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study results revealed the incidence of B. cereus isolates as 29.33 per cent in meat and meat products which are in agreement with similar incidence reported by Schlegelova et al, (2003) and Tewari et al, (2013), who too reported an incidence of 28 per cent and 30.9 per cent respectively in meat samples. However, Bedi et al, (2004) and Kamat et al, (1989) reported an incidence of 63.2 per cent and 80 per cent respectively in chicken and meat products.…”
Section: Antibiogram Of B Cereus Isolatessupporting
confidence: 92%
“…However, Willayat et al, (2007), who examined 200 raw mutton and cooked mutton samples found that 47 samples were positive for isolation and further results revealed that contamination of raw meat with Rather et al, (2011), who confirmed 59 (98.3 %) isolates out of 60 by targeting gyrB gene by using PCR. Similarly Tewari et al, (2013) confirmed 29 (100 %) isolates by targeting species specific gyrB gene which supports the results of the present study.…”
Section: Antibiogram Of B Cereus Isolatessupporting
confidence: 90%
“…The prevalence of the hblACD and nheABC complexes in our B. cereus isolates was lower than that obtained by Tewari et al. (). In this study, the detection rates of the hblA , hblC , and hblD genes in B. cereus were 25%, 37.5%, and 37.5%, respectively.…”
Section: Discussioncontrasting
confidence: 88%
“…Among the Bacillus species, B. cereus is a main cause of foodborne emetic and diarrheal diseases due to its enterotoxins and emetic toxins. Previous studies have indicated that B. cereus from various foods commonly has the nheABC , hblACD , and cytK genes (Guinebretiere, Broussolle, & Nguyen‐The, ; Kim et al., ; Tewari et al., ; Yim et al., ). In this study, 25% of the B. cereus isolates had all three genes of HBL and NHE complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Tewari et al (2013) reported 30.9 % overall incidence of B. cereus in various meat and meat products, while the recorded incidences of B. cereus from raw meat and meat products samples were 27.8 and 35 %, respectively.…”
Section: Scenario Of B Cereus Food Poisoning In Indiamentioning
confidence: 92%